Ligand-induced chirality and optical activity in semiconductor nanocrystals: theory and applications - Gounko, Iouri (Walter de Gruyter GmbH, 2020)
Chirality is one of the most fascinating occurrences in the natural world and plays a crucial role in chemistry, biochemistry, pharmacology, and medicine. Chirality has also been envisaged to play an important role in nanotechnology and particularly in nanophotonics, therefore, chiral and chiroptical active nanoparticles (NPs) have attracted a lot of interest over recent years. Optical activity can be induced in NPs in several different ways, including via the direct interaction of achiral NPs with a chiral molecule. This results in circular dichroism (CD) in the region of the intrinsic absorption of the NPs. This interaction in turn affects the optical properties of the chiral molecule. Recently, studies of induced chirality in quantum dots (QDs) has deserved special attention and this phenomenon has been explored in detail in a number of important papers. In this article, we review these important recent advances in the preparation and formation of chiral molecule-QD systems and analyze the mechanisms of induced chirality, the factors influencing CD spectra shape and the intensity of the CD, as well as the effect of QDs on chiral molecules. We also consider potential applications of these types of chiroptical QDs including sensing, bioimaging, enantioselective synthesis, circularly polarized light emitters, and spintronic devices. Finally, we highlight the problems and possibilities that can arise in research areas concerning the interaction of QDs with chiral molecules and that a mutual influence approach must be taken into account particularly in areas, such as photonics, cell imaging, pharmacology, nanomedicine and nanotoxicology.
PUBLISHED
Keywords: Nanomedicines; Colloidal nanocrystals; Induced chirality; Nanoplatelets; Optical activity; Quantum dots; Quantum rods; Chirality